Health literacy and health-related quality of life: The mediating role of irrational happiness - Huseynov, Amil; Satici, Begum (DE GRUYTER POLAND SP Z O O, 2025)
Background: Health literacy (HL) and irrational beliefs about happiness significantly influence adults' health-related quality of life (HRQoL). The purpose of this study was to examine whether irrational happiness mediates the relationship between HL and HRQoL among adults. Methods: A total of 686 adults (468 women and 218 men; mean age = 22.30 +/- 6.83 years) completed self-report questionnaires, including the Health Literacy Scale-Short Form, the EUROHIS-QOL 8, and the Irrational Happiness Beliefs Scale. Data were analyzed using structural equation modeling and bootstrapping methods. Results: HL had both direct (beta = 0.260, p < 0.01) and indirect effects on HRQoL. HL directly predicted irrational happiness (beta = -0.369, p < 0.01), which in turn directly predicted HRQoL (beta = -0.318, p < 0.01). Specifically, irrational happiness significantly mediated the relationship between HL and HRQoL (bootstrap coefficient = 0.117, 95% CI = 0.071-0.175). Conclusion: These findings suggest that interventions aiming to enhance adults' HRQoL should consider not only improving HL but also addressing irrational beliefs about happiness.
Keywords: health-related quality of life; health literacy; irrational happiness; structural equation modeling; PHYSICAL-ACTIVITY; General & Internal Medicine